Impact of primary headaches on subjective sleep parameters among adolescents - Gupta Ravi; Bhatia Manjeet; Dahiya Devendra; Sharma Sameer; Sapra Rahul; Semalti Kapil; Dua Raman Preet (Annals of Indian Academy of Neurology, 2008)
Context: Headache patients commonly report sleep disruption and sleep disorders. Available literature suggests that the sleep pattern of headache sufferers is different from the control group. Patients in these studies were recruited from headache clinics; they did not include tension type headache. Aims: The aim of this study is to find out whether primary headaches affect sleep patterns. Settings and Design: Community based cross sectional study Materials and Methods: This study was conducted in three high schools. Children in the 12-19 age group were allowed to participate. They were given a questionnaire in the presence of at least one of the authors, who assisted them in filling it. They were asked to provide responses based on most severe recurrent headache that they had experienced rather than the more frequent ones. The questionnaire included questions regarding demographic data and the characteristics of headache according to International Classification of Headache Disorders-2 criteria. Part B of the questionnaire contained questions regarding sleep habits. The children were asked to provide data regarding sleep habits on a normal school day. Diagnosis was based upon the information contained in the questionnaire. A telephonic interview was also done, where the information provided was found inadequate. Statistical Analysis Used: Analysis was done with the help of SPSS v. 11.0., descriptive analysis, Chi square, and one way ANOVA with post hoc analysis. Kruskall-Wallis tests were run. Results: A total of 1862 subjects were included in the study. Migraineurs and tension type headache sufferers comprised 35.7% and 13.4% of the group respectively. Migraineurs had the highest prevalence of nocturnal awakenings ( P < 0.001), abnormal movements ( P =0.001) and breathing problems during sleep ( P < 0.001). Approximately half the migraineurs felt sleepy during the day ( P < 0.001) and spent around 1.17 hours in sleep during the day ( P = 0.007). Similarly, values for frequency of nocturnal awakenings per week ( P < 0.001), wake time after sleep onset and offset ( P < 0.001 and 0.002 respectively) were the maximum in migraineurs. Only 32.8% migraineurs reported refreshing sleep ( P < 0.001). Post hoc analysis revealed that migraineurs were different from the other two groups on most of the parameters. Conclusions: Sleep disruption is more common in migraineurs than those in the tension type headache sufferers and the control group.